Filterless frequency 32-tupling millimeter-wave generation based on two cascaded dual-parallel Mach–Zehnder modulators - Chen, Xinqiao; Dai, Siyuan; Li, Zhihan; Liu, Xiaorui; Chen, Xu; Xiao, Huaibao (Frontiers in Physics, 2023)
A novel scheme for filterless frequency 32-tupling millimeter wave (MMW) generation based on two dual-parallel Mach-Zehnder modulators (DPMZMs) cascaded is proposed. When the MZMs are biased on maximum transmission point and the phase difference of the radio frequency (RF) driving voltage between the two MZMs in DPMZM is 2  , the DPMZM can be used as a quadrupler which can generate ±4n-order optical sidebands. When the phase difference of the RF driving voltage between the two DPMZMs is 4 , the two cascaded DPMZMs can be used as an octupler which can generate ±8n-order optical sidebands. After the ±8th-order optical sidebands are suppressed by adjusting the modulation index of MZMs, the center carrier is suppressed by a polarization multiplexing structure, and the ±8n (n＞2) sidebands are ignored because their amplitude are very small, the main optical components remained in the output of the two cascaded DPMZMs are ±16th-order optical sidebands which are beaten in the photodetector to obtain frequency 32-tupling MMW. The optical sideband suppression ratio (OSSR) and the radio frequency spurious suppression ratio (RFSSR) of the obtained signal in theory and experiment are 53.7 dB, 53.53 dB and 47.7 dB, 47.33 dB, respectively. The experimental and theoretical analysis is consistent that verifies the feasibility of the scheme. The influence on the OSSR and RFSSR of the generated signals by the extinction ratio and DC bias drift of the MZMs, the initial phases and the amplitudes of the RF drive signal, the azimuth of the polarization controller (PC) are investigated.Millimeter wave (MMW) • Mach-Zehnder modulator (MZM) • Dual-parallel Mach-Zehnder modulation (DPMZM) • Optical sideband • Frequency multiplication factor (FMF) • Optical sideband suppression ratio (OSSR) • Radio frequency spurious suppression ratio (RFSSR)